(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Burn injury remain one of the commonest forms of injury and account for a significant proportion of trauma cases in hospital emergencies worldwide. In the United States, up to 1.2 million people experience burn injuries each year.However, continue to cause devastating morbidity and significant mortality. Methodology: A descriptive analytic study design is carried out to explore the common causes of burn injuries among patient which conducted at AL-Imam AL-Sadiq Hospital for the period (15/1/2020- 15/3/2020). Non-probability Convenient sample consisted of (50) patients who admitted to the Burn Center is selected through the used probability sample approach. Result: (50) subject who participated in this study their age ranged from (20-29) years old and constituted (40.0%) of the study sample. Concerning gender, most burned participants were female, which composed (78.0%) and lives in urban areas (60.0%) out total number. Twenty-eight percent were primary school graduated and sixty six were married they work as students. Conclusion: common causes of burn as maximum incidence of burn injury seen in females in adult age group from (20-29) years old and lives in urban area. Most burned patients were primary school graduated and they were married and were burned by flame with moderate in severity. Recommendation: Development of strategy for burn prevention by the Ministry of Health because it is better way that makes people more aware and cautious when dealing with risks and preventing as much as possible exposure to risks and injuries.